Cinchona-catalysed, Enantioselective Synthesis of β-Peroxycarboxylic Acids, β-Peroxyesters and β-Peroxyalcohols - O128;™Reilly, Kate; K. Gupta, Manoj; K. Gandhi, Hiren; P. Kumar, Vydyuta; S. Eccles, Kevin; E. Lawrence, Simon; P. O128;™Sullivan, Timothy (Current Organic Chemistry, 2016)
A cinchona-catalysed, enantioselective oxa-Michael reaction of α,β-unsaturated aldehydes with either tert-butyl hydroperoxide or cumene hydroperoxide was developed. The reaction was optimised by screening of solvents, modification of the catalyst framework and variation of the acid co-catalysts. A strong relationship was noted between the pKa of the acid co-catalyst and the degree of selectivity. Enantioselective peroxidation of α,β- unsaturated aldehydes with tert-butyl hydroperoxide afforded β-peroxyaldehydes with good enantioselectivities. In situ oxidation of the latter compounds furnished β-peroxycarboxylic acids in high yields. Enantiomeric excesses were determined by derivitisation to their mandelate esters and subsequent separation by chiral high performance liquid chromatography. Peroxidation with cumene hydroperoxide was similarly successful with the products being isolated as stable β-peroxyalcohols. These latter β-peroxyalcohols offer a direct route to 5-membered, chiral cycloperoxides via a silver-mediated cyclisation. This reaction proceeds by trapping of the oxygen lone pair by the incipient carbocation followed by loss of the cumyl or tert-butyl group and formation of the cycloperoxide product.
Keywords: peroxyalcohols